2023
DOI: 10.5483/bmbrep.2023-0072
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib prevents the development of emphysema in a murine elastase model

Abstract: Emphysema is a chronic obstructive lung disease characterized by inflammation and enlargement of the air spaces. Regorafenib, a potential senomorphic drug, exhibited a therapeutic effect in porcine pancreatic elastase (PPE)-induced emphysema in mice. In the current study we examined the preventive role of regorafenib in development of emphysema. Lung function tests and morphometry showed that oral administration of regorafenib (5 mg/kg/day) for seven days after instillation of PPE resulted in attenuation of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Regorafenib, as a multitargeted tyrosine kinase inhibitor, is gradually being discovered to have potential curative effects in animal models of pulmonary emphysema, pulmonary hypertension, autoimmune arthritis, and Alzheimer’s disease . Given its established antitumor properties, exploring regorafenib’s utility in noncancerous diseases is of significant scientific interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regorafenib, as a multitargeted tyrosine kinase inhibitor, is gradually being discovered to have potential curative effects in animal models of pulmonary emphysema, pulmonary hypertension, autoimmune arthritis, and Alzheimer’s disease . Given its established antitumor properties, exploring regorafenib’s utility in noncancerous diseases is of significant scientific interest.…”
Section: Discussionmentioning
confidence: 99%
“…5 The high prevalence and serious complications of this condition underscore the urgent necessity for innovative therapeutic strategies aimed at managing osteoclast-related osteolytic diseases. Regorafenib, as a multitargeted tyrosine kinase inhibitor, is gradually being discovered to have potential curative effects in animal models of pulmonary emphysema, 53 pulmonary hypertension, 54 autoimmune arthritis, 55 and Alzheimer's disease. 56 Given its established antitumor properties, exploring regorafenib's utility in noncancerous diseases is of significant scientific interest.…”
Section: Discussionmentioning
confidence: 99%
“…In complementary studies, the potential of regorafenib was shown in a porcine pancreatic elastase (PPE)‐induced model of emphysema. Treatment with regorafenib (5 mg·kg −1 ) attenuated the senescence profile with reduced SA‐β‐Gal staining and p16 INK4a expression and improved PPE‐induced emphysema in mice (Oh et al, 2023 ; Park et al, 2023 ). To the best of our knowledge, there is no experimental data on the effects of regorafenib on the circadian rhythm in a disease setting.…”
Section: Possible Senotherapeutic Treatments For Copd‐induced Acceler...mentioning
confidence: 99%